PENGARUH KEPUASAN PELANGGAN, INOVASI PRODUK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN EMINA DI KOTA SOLO - NADIA AMBARSARI, ANITA (JURNAL WIDYA GANECWARA, 2020)
This  study  aims   to  determine  the  effect   of  customer  satisfaction,  product innovation  and   brand  image  on  Emina  customer   loyalty  in  Solo  city.  The subjects of this study were 97 respondents who were Emina users. Data collection methods to determine the  effect of customer  satisfaction, product innovation and customer loyalty   using a questionnaire. The   results of this study  indicate that customer satisfaction, product innovation, and  brand image  simultaneously and significantly influence customer loyalty for Emina products. Customer satisfaction partially has  a positive and  significant   effect on customer loyalty of Emina products. Product innovation does not have a positive and significant   effect on customer loyalty of Emina products. Brand image has a   positive and  significant effect  on customer loyalty  of Emina products.